The Meaning of Silence for Mastering the Practitioner's Reflective Skills - Maria Szymańska (Ignatianum University Press, 2021)
The aim of the article is to show the meaning of practicing silence, enhancing the quality of the reflective skills of the reflective practitioner. These skills - being, speaking, disclosing, testing, and probing - reveal one's reflective competences, which require time and silence to be developed. The reflective practitioner is a person who can creatively interact with their true-self, others, the world, and God. Therefore, he or she finds time to distance themselves from many stimuli that bombard the mind and the outer environment and treats silence and quietness more as a challenge, rather than a threat to their own existence. Silence, perceived as a space for finding a new quality of one's identity, is presented in the paper in different perspectives. The meaning of listening silence is especially worth noticing in the domain of education, which is preoccupied with large streams of information coming from varied sources that demand to be acquired. That is why this goal seems important for those who must cope with matters connected with teaching, learning, upbringing, and development. I attempt to deal with this briefly in a theoretical, practically-oriented analysis by suggesting some solutions covered in the material below.